Impact on the hepatic flow velocity after pediatric combined liver‐kidney transplantation compared to isolated pediatric liver transplantation—A matched‐pair analysis. Issue 10 (9th October 2019) - Hellenkemper, Jessica V.; Grabhorn, Enke; Brinkert, Florian; Lenhartz, Henning; Herrmann, Jochen; Fischer, Lutz; Helmke, Knut; Herden, Uta
Abstract: Background: Combined liver‐kidney transplantation (CLKT) in children is still a rarely performed procedure. Our aim was to analyze the effect of the simultaneous transplantation of the kidney in pediatric CLKT on the liver graft flow velocity, and vascular complications compared to singular liver transplantation (LTX) in children. Methods: All pediatric CLKT performed at our institution from 1998 to 2016 were matched with singular LTX and retrospectively analyzed. Results: Overall 30 CLKT were performed in 28 children (median age 8 years, range 1‐16) and matched with 30 children undergoing singular LTX (median age 7.9 years, range 1‐16). No significant differences were found concerning the systolic peak flow velocity of the hepatic artery (HA) or the resistance index (RI). Vascular complications of the hepatic vessels occurred in 16.7% (CLKT) and 6.7% (LTX). The 1‐/5‐ and 10‐year patient survival was 93.3%/93.3% and 93.3% (CLKT) and 100%/100% and 92.9% (LTX). 1‐/5‐and 10‐year liver graft survival was 76.7%/73.2% and 73.2% (CLKT) and 84.4%/75.9% and 69.6% (LTX). Conclusion: The simultaneous transplantation of the kidney in CLKT had no negative impact on hepatic flow velocity or vascular complications. Frequent Doppler ultrasound examinations, accurate volume management, and avoidance of abdominal pressure might be an explanation for the results and an excellent graft‐ and patient survival.